Pengaruh Kualitas Aplikasi Sistem Informasi Akademik (SIAKAD) Institut Daarul Qur’an Terhadap Kepuasan Mahasiswa - Marzuki; Anwar Sani, Muhammad (Jurnal Sistem Informasi, 2024)
Research was conducted to measure user satisfaction with the quality of the Siakad IDAQU Jakarta application using the Green and Pearson method and Multiple Linear Regression as data analysis techniques. All users of the IDAQU Jakarta application are involved, namely. campus leaders, lecturers, staff and students. A sample of 90 people was taken using disproportional stratified random sampling. Based on the results of data analysis, it is known that the regression coefficient on the variables ease of use, customization, download delay and content is positive, meaning that when the values of the four variables improve, user satisfaction will increase. Meanwhile, the user evaluation results for each questionnaire indicator are quite strong with an interpretation scale of 70% - 84%, which means that users are satisfied with the IDAQU Jakarta application, so the application is suitable for use as a student monitoring tool in the future.